Impacts of urban morphometric indices on ventilation. (1st February 2023) - Duan, G.; Nakamae, K.; Takemi, T.
Abstract: Ventilation has shown strong sensitivity to urban geometrical heterogeneity; however, the quantitative connection with the urban morphometric indices, e.g. the packing densities ( λ f and λ p for the frontal and plan area, respectively) and the building-height variability ( σ H ), remains unclear. Using large-eddy simulation (LES), the dispersion of a pollutant scalar is investigated for turbulent boundary-layer (TBL) flows developed over real urban regions. While the time history of the domain averaged concentrations follow the familiar exponentially decaying function for all cases, the decay rates differ and there is a clear monotonic dependence on λ f . The mean tracer age, τ a, exhibits a strong linear scaling with λ f as well ( R 2 = 0 . 8 ); however, an unambiguous relationship is hard to be discerned for the ventilation timescales versus the other morphometric indices (e.g. λ p and σ H ). An effective canyon aspect ratio ( A R eff ) is proposed for real urban districts, which allows ventilation to be quantified in a simpler manner as that for idealised canyons. The age spectrum, which measures the probability density function of tracer ages across multiple timescales, is analysed to reveal the mechanisms underlying the well-defined connection between ventilation and λ f . Results are compared with that for an aligned building array of an equivalent canyon aspect ratio to A R eff . The departures reflect the nonlinear effects that are not captured in idealised urban topography setups. The results could be useful for the parameterisation of ventilation in urban areas of complex geometrical profiles and may serve as a reference for urban layout design towards optimum active ventilation capability. Highlights: Pollutant decay rate exhibits strong linear scaling with the frontal-area density. Ventilation does not show conclusive dependence on building-height variability. Effective canyon aspect ratio is proposed for realistic urban districts. Age spectrum deviates from that for an aligned array of equivalent aspect ratio.